On Farm Assessment of INM Techniques on Soil Health and Yield of Rice in Sahibganj, Jharkhand - Jha, Amrit Kumar; Kumar, Anjani; Mehta, Birendra Kumar; Kumari, Maya; Chatterjee, Kaushik (Indian Journal of Extension Education, 2021)
On-farm trial was conducted to assess the Integrated Nutrient Management (INM) techniques on yield of rice and soil health after harvest during 2018-19 and 2019-20 at ten locations. The result of three treatments viz. Farmer’s Practice, Technology Option 1 and Technology Option 2 indicated that TO1 and TO2 significantly increased the yield and yield attributing characters over farmer’s practice (FP). Significantly high yield of rice grain (41.2 q per ha) was recorded with INM techniques. The data on available N, P and K status of soil after harvest of rice crop was significantly higher under TO2 as compared to FP. Highest net-return (Rs. 44,214 per ha) with B:C ratio of 2.44 was reported under TO2. INM techniques also resulted in lowest technology gap (8.78 q per ha) and technology index (17.56%) over other treatments which suggests it’s feasibility at farmer’s field.
Keywords: INM techniques; Grain yield; Soil health; Extension gap; Technology gap; technology index; benefit-cost ratio